Nucleotide sequence analysis of pRC12 and pRC18, two theta-replicating plasmids harbored by Lactobacillus curvatus CRL 705 - Teran, Lucrecia Cecilia (2020)
The nucleotide sequences of the two plasmids pRC12 and pRC18, harbored by thebacteriocin-producer Lactobacillus curvatus CRL 705, were determined and analyzed. Both plasmids belong to the theta-type replicating group and are present at low copy number. pRC12 is a pUCL287-like plasmid that possesses iterons and the repA and repB genes for replication while in pRC18 a pUCL287-like repA gene is disrupted by an 11 kb insertion, encompassing genes coding for a 168 amino acid replication protein affiliated to RepB which was named RepB?, several transposases/IS elements,and the lactocin Lac705 operon. Although the two plasmids share a region with high DNA identity level (> 83% identity between RepA, a Type II toxin-antitoxin system and a tyrosine integrase genes) both are stably maintained in their natural host L. curvatus CRL 705. An Escherichia coli / Lactobacillus shuttle vector carrying the pRC18 replicon (i.e. repB? and replication origin), a chloramphenicol resistance gene, and a pBluescript backbone was constructed and used to define the host range of RepB?. Chloramphenicol-resistant transformants could be obtained after electroporation of Lactobacillus plantarum CRL 691, Lactobacillus sakei 23K, L. curvatus CRL 1890 and a plasmid cured derivative of L. curvatus CRL 705, but not Lactococcus lactis NZ9000.Depending on the host, transformation efficiency ranged from 101 to 108 per µg and the plasmid was then relatively stable as 29-53% of recombinants kept it after growth for 100 generations without chloramphenicol selective pressure. This shuttle vector could therefore be used for cloning and functional studies in several Lactobacillus species.